Does Crowd Support Drive the Home Advantage in Professional Football? Evidence from German Ghost Games during the COVID-19 Pandemic. (December 2021) - Fischer, Kai; Haucap, Justus
This paper examines the relation between crowd support and home advantage in men's professional football in making use of a unique "natural experiment" induced by restrictions due to the COVID-19 pandemic: the so-called ghost games in the top three German football divisions at the end of the 2019/2020 season. We find that there is a reduced home advantage in the first division, whereas no change is observed in the second and third divisions. Our regression analysis indicates that the decrease in the home advantage and the heterogeneity across divisions are not sensitive to a variety of performance, location, and team covariates and are best explained through the lower occupancy rate in the stadia. Hence, the decrease in occupancy to zero at the ghost games has been less dramatic for teams that have been used to low occupancy rates. We cannot find strong evidence for a change in referee behavior or teams' tactics as main impact channels of occupancy rates on the home advantage. Hence, we argue that psychological reasons are of higher importance.